Deposit Money Banking Financing And Its Effect On Real Sector Output In Nigeria: Evidence From Trade And Agricultural Sectors - Arikpo, Oka Felix; Adebisi, Adesola W. (Advances in Social Sciences Research Journal, 2017)
This study examined the effects of deposit money banks financing on real sector output in Nigeria. The study specifically assessed the effect of private sector credit, interest rate spread, deposit mobilization and banks’ holding of treasury bills on trade and agricultural sectors outputs in Nigeria. The data for the study were source from the CBN statistical bulletin for the period 1984 to 2015. The exploratory design was combined with the ex-post facto research design; the data collection method was desk survey. The study used the Vector Error Correction Mechanism (VECM) for data analysis. Findings showed that jointly, deposit money banks financing have a long term significant effect on the trade sector but does not have any long run effect on the agricultural sector in Nigeria. Also, it was revealed that there is no short run causality running from PSC, DMB, DTB and INTS to agricultural sector output; however only INTS has short run causality with trade sector output. Lastly, interest rate spread has an inverse effect on the trade sector output but a positive effect on the agricultural sector output in Nigeria. The study therefore recommends that Deposit money banks should in addition to granting loans to farmers; monitor the use of such funds to avoid loan diversion and consequently poor agricultural sector performance. Also, Banks should employ research staff to conduct researches on modern approaches to effective real sector production and investments and should use the research findings to train her loan customers on the best production techniques as this will go a long way to enhance the real sector output. Lastly, the spread between lending and deposit rates should be narrowed to trigger savings and enhance banks’ loan supply and real sector loan demand which consequently will boost productivity in the real sector.